Características clínicas e prevalência de sensibilização a alérgenos alimentares e inalantes em pacientes pediátricos portadores de esofagite eosinofílica - Rezende, Érica Rodrigues Mariano de Almeida (2011)
Eosinophilic Esophagitis (EoE) is a pathological clinical emerging disease, whose recognition has nearly three decades. It is defined as a chronic inflammatory disorder, immune mediated characterized by primary esophageal symptoms of upper gastrointestinal tract dysfunction, associated with an increase of eosinophils intra-epithelial lymphocytes in esophageal mucosa, in number exceeding fifteen eosinophils by large field of increase, in more than a fragment of biopsy obtained during the examination of digestive endoscopy. The prevalence and incidence of EoE in Brazil is unknown. Describing the clinical, endoscopic, histological aspects, epidemiological and evaluate awareness allergic foods and inhalants of patients in the pediatric age group, was the goal or object of this research, with prior diagnosis of EoE, 35 of them were evaluated in the period from January 2010 to January 2011. Responsible for patients filled a form with questions and patients performed tests for evaluation of IgE and not IgE allergic awareness mediated foods and a test to assess immediate allergic awareness through inhalants, with skin prick test (SPT) and atopic patch test (APT) . Most epidemiological, clinical, histological characteristics was similar to those observed in world literature, except the upper endoscopy for diagnosis of EoE perception in patients studied, reported on 97.2% of endoscopic examinations carried out and confirmed by histological examination. Sensitization feeding evaluated through the APT and SPT was 46%, lower than the observed in the literature, being expressive the presence of awareness inhalants, observed in 66% of the patients evaluated. The foods most frequently involved in awareness observed in the tests performed were the cow's milk, soybeans, fish and chicken meat. A group of eight patients (22.8%), awareness has not submitted any of the allergens tested, showing characteristics in relation to sex, presence of atopic dermatitis associated examination of pHmetria of 24 hours normal findings of clinical and endoscopic with difference statistically significant in relation to the group aware.